Representation of the Objectification of Teenage Female Characters in Sofia Coppola's Film - Endah Wulandari (Sean Institute, 2025)
This study examines the representation of objectification of teenage female characters in Sofia Coppola's film, The Virgin Suicides (1999). The study employs feminist theory, focusing on Martha Nussbaum's (1995) classification of objectification and Laura Mulvey's (1975) theory of the male gaze. Mise-en-scène is the primary framework for describing the representation of objectification experienced by the Lisbon princesses.The analysis shows that the film consistently uses mise-en-scène to depict the objectification of the Lisbon princesses as objects for the fulfillment of male desires and fantasies. The study identifies six of the seven forms of objectification defined by Nussbaum, with instrumentality, inertness, and fungibility as the most dominant.